Building of Virtual Multidocuments Mapping to Real Sources of Data in Situation-Oriented Databases - Mironov, Valery; Gusarenko, Artem; Yusupova, Nafisa (Modern Information Technology and IT Education, 2021)
Within the framework of the Polyglot Persistence approach, a situationally-oriented database is considered - an information processor within a web application that processes XML/JSON documents based on the HSM hierarchical situational model. A flexibility task in HSM of mapping virtual documents for real data from various physical storages is discussed. In order to embed new data warehouses, it is suggested to follow the principle of invariance, the model does not change when embedding a new mapping. An approach mapping embedding is proposed, which provides for each new type of storage the development of three modules: manipulation, loading and saving, implemented as callback functions. To embed three modules working with the repository, a common plug-in technology is used. The approach is illustrated by the example of mapping to the table of the relational database SQLite. The advantages of the approach and practical implementation on the PHP platform are discussed and demonstrated on SQLite database.